The Relationship Between the Role of Nurses as Educators and the Level of Adherence to Taking Medication in Diabetes Mellitus Patients at RSUD Dr. Moewardi Surakarta - Kusuma, Aurrell Adna; Purwanti, Okti Sri (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Diabetes mellitus (DM) is a chronic disease caused by impaired insulin production or utilization, leading to serious complications if not properly managed. Non-compliance with medication remains a major challenge, contributing to poor outcomes and increased mortality. Nurses play a pivotal role as educators in improving patient adherence. Objective: To examine the relationship between the role of nurses as educators and medication compliance among DM patients. Methods: A quantitative cross-sectional study was conducted on 129 DM patients at the Endocrinology Polyclinic of Dr. Moewardi Regional Hospital, Surakarta, from November to December 2024. Data on nurses’ educational roles and patients’ medication compliance were collected using structured questionnaires, including the validated Morisky Medication Adherence Scale (MMAS-8). The Spearman Rank test was used for analysis. Results: The analysis revealed a significant positive relationship between the role of nurses as educators and medication compliance (p = 0.001; Rho = 0.634). Although most respondents (97.7%) rated the nurses’ role as “good,” more than half (54.2%) still demonstrated moderate to poor compliance. Conclusion: Nurses’ educational role has a strong positive impact on medication compliance in DM patients. Strengthening and sustaining educational strategies are essential to improve adherence and health outcomes